Legal Status of Land Rights Certificates due to Neglect by Rights Holders and Decades of Occupation: A Normative Legal Study - Aslan Noor; Avif Prasetyo; Rais Rahmat Nugraha; Siti Nurhasanah; Celeste M. Navarro (Faculty of Law, Universitas Pekalongan, 2025)
This study analyses the legal status of land title certificates when their holders neglect the land, allowing it to be occupied by the community for decades. Based on a normative legal approach, this study examines primary legal materials (laws and regulations and court decisions) and secondary materials (scientific literature) to examine the relationship between legal certainty, the social function of land, and administrative corrective mechanisms. The results show that certificates are strong evidence but not absolute because their validity is conditional on the accuracy of physical-legal data and the holder's compliance with social functions. Neglect (land not used/utilised/maintained) opens up the possibility of land being declared abandoned and rights revoked through administrative procedures, while long-term occupation by the community gives rise to the need for normative-factual assessments that balance formal certainty and substantive justice. This study identifies misunderstandings about the certainty of certificates as triggers for abandonment and escalation of disputes when rights holders seek to restore physical control. It recommends prevention based on utilisation plans, boundary and data validation (title validation), collaborative mapping, and transparent and standardised administrative enforcement. Policy implications emphasise education on social functions, modernisation of land administration, and compensation/guarantee mechanisms that maintain public trust without neglecting rights protection. The findings enrich the land reform discourse with an operational testing framework.